Ecological niche modeling for assessing potential distribution of Pterocarpus marsupium Roxb. In Ranchi, eastern India. Issue 6 (22nd September 2020) - Kumar, Amit; Kumar, Anish; Adhikari, Dibyendu; Gudasalamani, Ravikanth; Saikia, Purabi; Khan, Mohammed Latif
Abstract: The present study was conducted to predict the current and future potential distribution of a tree species Pterocarpus marsupium Roxb. in Ranchi, Eastern India using ecological niche modeling. Nine environmental variables comprising of isothermality, precipitation of wettest and warmest quarter, annual temperature range, soil type, human influence index, elevation, slope and land use cover were used to model the distribution of the species. Climatic variables governed the predicted distribution of the species as they contributed 56.7% as compared to the other nonclimatic variables (43.3%). Northern parts exhibited the most suitable niche of the species as compared to south‐east and central parts that showed low probability of occurrence due to high disturbances caused by rapid urbanization as well as over exploitation of the species for timber, edible and medicinal uses. The average test area under the receiver operating curve (AUC) (0.921) as well as the partial AUC indicated good model performance. The projected change scenarios of RCP2.6, RCP4.5 and RCP6.0 for the year 2050 reveal that the climatically suitable areas will be drastically reduced in Ranchi. The population of the species is declining due to its exploitation from natural habitats for timber and medicinal uses and is listed as near‐threatened by the current IUCN‐Red lists. The findings of this paper will help to identify the potential habitats for further conservation of this near‐threatened species in the changing climatic conditions and increasing anthropogenic pressure. Abstract : The overexploitation of Pterocarpus marsupium Roxb. for its timber and medicinal uses leads to inclusion in IUCN‐Red lists as near threatened species. The current and future potential distribution of P. marsupium ‐was predicted in Ranchi district, Eastern India using ecological niche modeling. Nineteen bioclimatic parameters, and five other environmental variables‐based niche modeling exhibited its high probability of occurrence in south‐western, and north‐western parts, whereas low probability of occurrence of the species in south‐eastern, and central parts due to high ecological disturbances. The future prediction exhibited the least probability of occurrence in the major parts in the region of its current distribution under climate change scenarios of RCP 2.6, RCP 4.5 and RCP 6.0.